Home Bound Working Women and Organizational Efficiency of Developing Economy - Babar Ansari; Kanwal Gul; Aamir F. Shamsi (Institute of Business Management, 2017)
This research aims to understand the preferences of educated unemployed women of Pakistan and India on the imposition of the law of "Flex time/rules for home bound educated women". For this purpose, 158 respondents were asked to fill a survey out of which 79 respondents were educated employed women and 79 respondents were unemployed women (79). Chi-square was applied to the data. Findings suggest that 94% of the women from both the groups are of the view that an introduction of women quota would result in an increase in women participation in the workforce. To understand management's perspective, 6 interviews with HR heads of selective industries were conducted. Narrative Analysis was applied which revealed only 10 to 20% women participated in the total workforce. The study also highlights reasons for low women participation. These include cultural norms, maternal issues, maternity problems, after marriage restrictions and childbirth. The study concludes that introducing an introduction of women quota in both public and private sectors would help increase women participation and contribution to the country's economy.